2010
DOI: 10.1080/09540121003605054
|View full text |Cite
|
Sign up to set email alerts
|

Social rebirth and social transformation? Rebuilding social lives after ART in rural Uganda

Abstract: This paper examines how HIV diagnosis, illness and anti-retroviral therapy (ART) have an impact on the social dimensions of people's lives in rural Uganda, focusing on identity, relationships and membership of groups. Using concepts drawn from sociological research on experiences of illness and recovery, "getting back to normal", "rebirth" and "turning point", we present findings from qualitative research that explored the social changes brought about by HIV and ART among 70 men and women taking ART since 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 20 publications
3
24
0
5
Order By: Relevance
“…Similar positive attitude towards life was also observed in PLHIV in study done by Robins et al 15 In studies done by Seeley et al observed that study participants in rural Uganda struggled to "get back to normal" and rebuild their social lives after a diagnosis of HIV and treatment. 16 However, study done in single city limits us to generalize the results. There is definitely a need for well-planned, large-scale studies using standardized methodologies to study perception of health status of People Living with HIV and quality of life.…”
mentioning
confidence: 99%
“…Similar positive attitude towards life was also observed in PLHIV in study done by Robins et al 15 In studies done by Seeley et al observed that study participants in rural Uganda struggled to "get back to normal" and rebuild their social lives after a diagnosis of HIV and treatment. 16 However, study done in single city limits us to generalize the results. There is definitely a need for well-planned, large-scale studies using standardized methodologies to study perception of health status of People Living with HIV and quality of life.…”
mentioning
confidence: 99%
“…Com o perfil de marginalidade econômica de muitos que vivem com HIV/aids, os quais, desempregados ou ocupando cargos com baixos salários, vê-se a importância da reconstrução das relações sociais, ou da manutenção das mesmas, as quais podem ajudar nas necessidades materiais, bem como no bem-estar emocional (COSTA; OLIVEIRA; FORMOZO, 2015a;SEELEY;RUSSELL, 2010).…”
Section: O Suporte Social E a Sua Relação Com O Hiv/aidsunclassified
“…Nesse sentido, sustentar vidas mudadas pelo HIV exige compreensão e apoio das organizações sociais, de amigos, de parentes e de conhecidos, os quais contribuem para amenizar os prejuízos emocionais e de suporte social (MELO et al, 2016;SEELEY;RUSSELL, 2010).…”
Section: O Suporte Social E a Sua Relação Com O Hiv/aidsunclassified
See 2 more Smart Citations